SOA Distributed Systems Architecture - Solarte Martinez, Guillermo Roberto (Scientia et Technica, 2021)
In business today, companies need to understand to great deal of permissiveness to adapt slightly to the rigid environment that demands of them. Traditional architectures have not provided adequate responses to this need because they Plough designed for to specific and limited purpose, under their integration is very complicated, making it difficult to quickly adapt processes to take advantage of new business opportunities and respond or prevent external threats. Today, to new way of conceiving information systems have surface, called Service Oriented Architecture (SOA), with the option of providing to better response under far, in order to provide organizations with the required permissiveness. In an SOA, the application functionality is provided through components called services, which have well-defined standard interfaces and represent business functions.